The Differences in Employees’ Perceptions of Transactional and Transformational Leadership Styles at CV. Makmur Abadi - Gwenn Louida Lee Pattinama (International Journal of Educational Research & Social Sciences, 2021)
The practice of leadership based on previous theories is not able to create a more fundamental change that is urgently needed today, such as changes in behavior, values, ​​and motivation. To address this need for change, theories of leadership are proposed and developed. They are transactional and transformational leadership styles. As known, an organization or company consists of various kinds of individuals who come from various statuses in society, which is in the form of education, position, class, experience, gender, and age. The differences in these characteristics affect the world of work so that the presence of these differences may cause the employees’ perceptions to differ from one another. This study aims to investigate the differences in perceptions of transactional and transformational leadership styles based on individual characteristics. Samples in this study were 98 employees of CV. Makmur Abadi. In addition, data were obtained through the distribution of questionnaires. The results showed that there were differences in employees’ perceptions based on age. However, there were no differences in employees’ perceptions based on gender, education level, type of education, department of work, and length of work.